Earnings persistence - Frankel, Richard; Litov, Lubomir (Journal of Accounting and Economics, 2009)
Dichev and Tang [2009. Earnings volatility and earnings predictability. Journal of Accounting and Economics, this issue, doi:10.1016/j.jacceco.2008.09.005] document the predictive power of past earnings volatility for the persistence of current earnings. We revisit their findings to verify the incremental explanatory power of this effect and to study whether the predictive power of past earnings volatility is priced in stock returns. We also discuss motives for the study of earnings persistence. Our findings indicate that the relation between past earnings volatility and earnings persistence is robust to the additional controls and to a correction for sampling bias, but that earnings volatility does not predict stock returns.